ISLAMIZATION OF KNOWLEDGE AND RELEVANTIZATION IN COMMUNICATION - Inah Inah (PASCASARJANA UNISNU, 2022)
Communication is a divine concept in Islam, with humans being the finest creature created by Allah SWT, blessed with the brain and all five senses, and communication serving as the unifying force. The science of communication has a very close relationship with da'wah, especially in terms of how religious messages are conveyed to the public. In terms of the method of delivering messages, da'wah and tabligh take the form of kitabah (journalist), khitabah (rhetoric), I'lam (drama, film, or cinema). To communicate Allah's message to people, the Qur'an uses terms such balàgh, da'wah, basher, nadhár, tadhkirah, and Mawi'zah. Wahy (revelation), the most central concept in the Qur'an, is a communication-related concept. Hence, the concept of communication in Islam is still relevant for the development of communication studies from an Islamic perspective. This study is the purpose of the field communication an Islamic perspective. There are two elements in the communication field which Islamic communication paradigm and the Islamic communication model.